Consumption of Fruit and Vegetable with Risk of Obesity in School-Age Children - Agnes Sevelina Anggraeni; Tintin Sukartini; Kristiawati Kristiawati (Universitas Airlangga, 2017)
Introduction: The problem of obesity in children aged 5-12 years in Indonesia is still high, East Java is one of the provinces that have a higher prevalence of obesity than the national average (Riskesdas 2013). Consumption of fruit and vegetables affects the level of obesity’s risk, but nowadays fruit and vegetable consumption in school-age children are low. This study was aimed to determine the correlation between consumption patterns of fruits and vegetables with the risk of obesity in school-age children in Ketabang I Surabaya elementary school.Methods: This research uses the descriptive correlation method with cross sectional approach. The population of this research is students in grade 4 and 5. Purposive sampling technique used to select 69 respondents as samples. The independent variable in this study is the consumption pattern of fruit and vegetable, while the dependent variable is the risk of obesity. The data were analyzed with chi-square test.Results: The results of this research showed that most of the respondents consume less fruit and vegetable (52%). The number of respondents who are obese is 20%, while the number of respondents who have high risk is 13%. Statistical analysis showed that the consumption pattern of fruits and vegetables has a correlation with the risk of obesity (p = 0.009).Discussion: There was a significant relationship between the consumption patterns of fruit and vegetables with risk of obesity in school-age children in Ketabang I Surabaya elementary school. Further studies should examine the appropriate interventions to overcome the problem of obesity in school-age children.